2023
DOI: 10.1002/jor.25508
|View full text |Cite
|
Sign up to set email alerts
|

Nonopioid pharmacological management of acute low back pain: A level I of evidence systematic review

Abstract: Acute low back pain (LBP) imposes a significant socioeconomical burden as it is the condition that, worldwide, cause the most disability. Nonetheless, the literature regarding the best pharmacological management of acute LBP is limited, and the indications available in the literature are conflicting. This work investigates whether the pharmacological management of acute LBP can effectively reduce pain and disability, and aims to identify which drugs show the highest efficacy. This systematic review was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Similarly, To Van Dut's research [6] from 2022 showed that the VAS index dropped from 7.1 to 4.2 after 15 days of treatment, which was statistically significant. Regarding the effectiveness of NSAIDS treatment, according to the findings of a meta-analysis study by Baroncini A [7], which showed a reduction from 6.9 to 2.0 following therapy (17.7 ± 24.9 days).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, To Van Dut's research [6] from 2022 showed that the VAS index dropped from 7.1 to 4.2 after 15 days of treatment, which was statistically significant. Regarding the effectiveness of NSAIDS treatment, according to the findings of a meta-analysis study by Baroncini A [7], which showed a reduction from 6.9 to 2.0 following therapy (17.7 ± 24.9 days).…”
Section: Discussionmentioning
confidence: 99%
“…LBP is one of the most common health problems among adults. Within 3 months, myorelaxants, nonsteroid anti-inflammatory drugs (NSAIDs), and NSAIDs with paracetamol can effectively reduce pain and disability in patients [ 28 ]. After 3 months, it can develop into CLBP.…”
Section: Discussionmentioning
confidence: 99%
“…For example, The American College of Physicians (ACP) recommends non-pharmacological care as the first option for people with LBP [ 14 ]. Several non-pharmacological therapies, such as exercise and various manual therapies, demonstrate similar benefits to pharmacological therapies with comparatively less risk [ 15 23 ] and lower healthcare costs [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%